INCREASING THE EFFICIENCY OF THE LABOUR RESOURCES USAGE OF AGROSECTOR ENTERPRISES IN THE SYSTEM OF SUSTAINABLE DEVELOPMENT OF THE RURAL TERRITORIES: A CASE STUDY OF UKRAINE - Tetiana SHMATKOVSKA; Anzhela NIKOLAEVA; Myroslava ZABEDYUK; Yuliia SHEIKO; Yuliia GRUDZEVYCH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the article it was found that during 2016-2019 in Ukraine the total productivity of agricultural workers increased, due to increased investment and technological renewal of agricultural production by large agricultural holdings. The main reason for this growth is the opening of access to Ukrainian agricultural enterprises to the markets of the European Union. Accordingly, the enterprises of the agricultural sector of Ukraine focus on the development of crop production, which is more attractive in terms of increasing profitability due to significant export opportunities. According to the obtained results, the amount of labour costs of employees in agricultural enterprises for the analysed period has generally more than doubled. In the article we have identified regional features of labour productivity of enterprises in the agricultural sector of Ukraine, in terms of studying the level of efficiency of staff use. We have substantiated the proposals for the introduction of a special algorithm in the activities of agricultural enterprises to ensure the efficiency of the management of their labour resources. We in the article proved that the improvement of the system of formation and use of labour resources of agricultural enterprises of Ukraine should also consider the identified regional disparities in the levels of labour productivity, in order to stimulate the productivity of enterprises in the regions with the lowest rates.